The geometry of continental displacement and its application to Arctic geology: Eugen Wegmann's early approaches published in the Geologische Rundschau in 1943 - Letsch, Dominik (2018)
Plate tectonics developed around 1965 as a powerful tool to describe the tectonic movements of the Earth's crust. The article demonstrates that basically four already existing theoretical concepts—subduction, seafloor spreading, the application of Euler's theorem and transform faults—had to be combined to arrive at the modern theory. Alfred Wegener, father of the theory of continental displacement, is often credited as the most direct forerunner of plate tectonics. However, none of the aforementioned concepts had been developed by him. The present article deals with the hitherto not duly credited contributions of the Swiss geologist Eugen Wegmann (1896-1982). He developed in a series of highly original papers published between 1943 and 1948 (one of them in the Geologische Rundschau), a critical test of the theory of continental displacement based on the regional geology of the Arctic. Furthermore, he gave a very concise account on the geometrical principles of drift movements. As a result, he developed for the first time—25years before McKenzie and Parker's Nature 216:1276-1280, landmark paper on the Pacific (1967)—the geometrical basis to graphically test plate motion directions. However, his work has not yet received the credit it deserves, neither by scientist nor by historians of science